2005
DOI: 10.1159/000087794
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Androgen Castration: A Biological Reality during Intermittent Treatment in Metastatic Prostate Cancer?

Abstract: Introduction: To assess the effects of intermittent maximal androgen blockade (IMAB) on testosterone (T) levels during on- and off-treatment periods. Materials and Methods: A total of 51 patients with metastatic prostate cancer underwent a 6-months period of continuous maximal androgen blockade (MAB) consisting of leuprorelin (3.75 mg at monthly intervals) plus flutamide (250 mg t.i.d.) followed by IMAB. During each cycle, the cut-off prostate-specific antigen (PSA) levels to stop and resume treatment were 4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…This is not so different from data obtained with other compounds [7,8]. It must be remembered that the minimum testosterone level required to avoid castration side effects is still unclear.…”
contrasting
confidence: 47%
“…This is not so different from data obtained with other compounds [7,8]. It must be remembered that the minimum testosterone level required to avoid castration side effects is still unclear.…”
contrasting
confidence: 47%
“…Intermittent ADT, for example, was associated with recovery of BMD in the off-treatment phase [87], a beneficial effect on cognitive function and depression [88,89], and an overall increase in general health-related QoL [90]. This is based on the fact that testosterone levels recover during off-treatment phases [91]. Because the majority of these studies are limited by relatively small sample sizes, it is currently unclear whether intermittent ADT may also reduce the incidence of severe side effects such as diabetes and cardiovascular morbidity.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The main concern of these studies is to understand the mechanism of treatment-resistant tumor growth, or a cancer relapse, after a remission period induced by hormone deprivation therapy. A possible strategy to delay or prevent the progression to hormone-resistance caused by prolonged hormone suppression is to incorporate treatment interruption, which is known as intermittent hormonal therapy repeating cycles of on-treatment and off-treatment periods [8][9][10][11][12][13][14][15]. In this paper, we deal with nonlinear dynamics and bifurcations in a mathematical model of intermittent hormonal therapy for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to understand the properties of androgen receptors and signal-transduction pathways leading to a hormone-refractory prostate cancer [20][21][22][23]. Intermittent androgen suppression (IAS) is an alternative approach to maintain tumor sensitivity to androgen deprivation with the possibility to prolong a relapse [8][9][10][11][12][13][14][15]. Although clinical trials are still in progress for establishing the clinical efficacy of IAS therapy [11,14,15], it has already been confirmed that side effects and economic costs are at least reduced in comparison with continued androgen suppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation